Insect Gut Bacterial Diversity Determined by Environmental Habitat, Diet, Developmental Stage, and Phylogeny of Host - Yun, Ji-Hyun (American Society for Microbiology, 2014)
Insects are the most abundant animals on Earth, and the microbiota within their guts play important roles by engaging in beneficial and pathological interactions with these hosts. In this study, we comprehensively characterized insect-associated gut bacteria of 305 individuals belonging to 218 species in 21 taxonomic orders, using 454 pyrosequencing of 16S rRNA genes. In total, 174,374 sequence reads were obtained, identifying 9,301 bacterial operational taxonomic units (OTUs) at the 3% distance level from all samples, with an average of 84.3 (±97.7) OTUs per sample. The insect gut microbiota were dominated by Proteobacteria (62.1% of the total reads, including 14.1% Wolbachia sequences) and Firmicutes (20.7%). Significant differences were found in the relative abundances of anaerobes in insects and were classified according to the criteria of host environmental habitat, diet, developmental stage, and phylogeny. Gut bacterial diversity was significantly higher in omnivorous insects than in stenophagous (carnivorous and herbivorous) insects. This insect-order-spanning investigation of the gut microbiota provides insights into the relationships between insects and their gut bacterial communities.